The value of Stilbestrol implants, Stilbestrol implants plus Aureomycin, and shelter for wintering steer calves - Smith, E.F.; Koch, B.A.; Richardson, D.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Forty-four good to choice Hereford steer calves from near Paducah, Texas, were assigned to four treatments on the basis of weight. All lots were fed identical high roughage rations. They received per head daily: 4.7 pounds of sorghum grain, 0.5 pound of soybean meal, 0.1 pound of bonemeal, and 3 pounds of alfalfa hay. Sorghum silage was fed according to appetite, and salt was offered free choice.
Keywords: Beef; Stilbestrol implants; Aureomycin; Steers